Métodos numéricos para equações diferencias ordinárias - Maioli, Gabrielle [UNESP] (2015)
The goal of this work is to explore the one-step numerical methods, called methods of Euler and Runge - Kutta, and the multistep numerical methods, called methods of Adams-Bashforth and Adams Moulton, for finding approximate solutions of initial value problems for first-order ordinary differential equations